IMPLEMENTATION OF NATIONAL INSTITUTE OF HEALTH GUIDELINES AND OTHER FACTORS CONTRIBUTING TO WORK-RELATED BURNOUT IN COVID ISOLATION WARD AND ICU PHYSICIANS - Hussain, Mulazim; Muhammad Bin Amjad; Juniad Ahsan; Shayan Omer Minhas (Journal of Ayub Medical College Abbottabad, 2021)
Background: During the pandemic, disruption of work schedule and constant health risks causes physician burnout. This study aims to identify Burnout in physicians working in COVID ICU and isolation Ward. Methods: A cross-sectional study was conducted on 200 physicians who had worked in either COVID ICU or Isolation ward. A survey of 23 questions was designed to assess the work-related Burnout using the Copenhagen burnout inventory and the implementation of NIH guidelines. Result: Among the 200 physicians, 151 (75.5%) were well informed of the guidelines, of which 52 (34.4%) participants believed the guidelines were not sufficient. These 34.4% of individuals showed a mean burnout score of 70.05% (p-value 0.001). Medical registrars and Medical Officers suffered the highest burnout mean percentage score of 76% and 72.42%, respectively. 89 (44.5%) individuals arranged PPE suits on their own and suffered a burnout score of 71.3% ±14.35 (p-value <0.001). Seventy-two (36%) claimed their administration was not cooperative in resolve safety issues. These individuals showed a mean burnout score of 74.3% ±13.82 (p-value <0.001). Conclusion: Lack of physician’s faith in the adequacy of the NIH guidelines has been found to be a significant factor in contributing to work-related Burnout. Due to the shortage of PPE, a majority of physicians have to reuse their PPE multiple times and even have to personally arrange their PPE suits, which further compounds the burnout. Increase administrative cooperation in resolving issues related to safety measures should help elevate work-related burnout in physicians working in the ICU and isolation ward.